Pengobatan Alternatif - Yasavati Kurnia Nah (Fakultas Kedokteran Universitas Kristen Krida Wacana, 2004)
Alternative to conventional medicine will always exist. Defined by its outsider status, alternative therapies of one era may become conventional therapies in another time. Alternative medicine ranges from system with distinct disease theories, diagnostic methods, and multiple treatment options, to singel-component panaceas, such as bee pollen. Although many unconventional therapies are not supported by rigorous prospective clinical trials, â€œalternativeâ€ is not synonymous with â€œunprovenâ€. The use of unconventional therapies is widespread. Usage is especially high among colored people, reflecting the fact that, for many, alternative therapies are traditional medicine.Key words : alternative medicine